Photoreceptor rhodopsin: structural and conformational study of its chromophore 11-cis retinal in oriented membranes by deuterium solid state NMR. - Gröbner, G; Choi, G; Burnett, I; Glaubitz, C; Verdegem, P; Lugtenburg, J; Watts, A (1998)
Rhodopsin is the retinal photoreceptor responsible for visual signal transduction. To determine the orientation and conformation of retinal within the binding pocket of this membrane bound receptor, an ab initio solid state 2H NMR approach was used. Bovine rhodopsin containing 11-cis retinal, specifically deuterated at its methyl groups at the C19 or C20 position, was uniaxially oriented in DMPC bilayers. Integrity of the membranes and quality of alignment were monitored by 31P NMR. Analysis of the obtained 2H NMR spectra provided angles for the individual labelled chemical bond vectors leading to an overall picture for the three dimensional structure of the polyene chain of the chromophore in the protein binding pocket around the Schiff base attachment site.